Tinjauan Kurikulum Pendidikan Sejarah Program Pascasarjana UNS - Agung, Leo (MIIPS, 2010)
Higher education curriculum is a set of plans and arrangements regarding the contentand study materials and lessons and ways of delivery and assessment are used to guide theteaching-learning activities in college. The curriculum is a program developed andimplemented to achieve an educational goal. So the curriculum can mean a program in theform of documents and program implementation. As a curriculum document (curriculumplan) was prepared in the form of details of the course, syllabus, learning design, systemevaluation of success. Moderate curriculum as an implementation program is a form oflearning, which obviously made (actual curriculum). The reason there are changes in the curriculum of internal and external factors. The steps penysunan curriculum are the following: (1) preparation of a graduate profile, ie the expected roles and functions can be run by graduates of the future in the community, (2)determination of competency based on the profile of graduates, (3) Determination of material related to the field study science and technology courses, (4) Determination of the depth and breadth of the study (credits) are done by analyzing the relationship between competence and the required study materials, (5) Combine the various study materials into courses, (6)Develop curriculum structure by means of distributing the course of the semester, (7) Develop a Learning Plan, and simultaneously (8)selecting appropriate learning method to achieve competence. Curriculum development has broad sense, which includes planning, implementation and evaluation. Curriculum designers can follow the advice in the Book of Common Prayer in which its adherents are required to "hold fast to what is good".